Comparison of DFT and ab initio QM/MM methods for modelling reaction in chorismate synthase - Narin Lawan (2018)
Quantum mechanics/molecular mechanics (QM/MM) methods are a popular tool in the investigation of enzyme reactions. Here, we compare B3LYP density functional theory (DFT) and ab initio QM/MM methods for modelling the conversion of 5-enolpyruvylshikimate-3-phosphate to chorismate in chorismate synthase. Good agreement with experimental data is only obtained at the SCS-MP2/CHARMM27 level for a reaction mechanism in which phosphate elimination precedes proton transfer. B3LYP predicts reaction energetics that are qualitatively wrong, stressing the need for ab initio QM/MM methods, and caution in interpretation of DFT results for this enzyme. © 2014 Elsevier B.V. All rights reserved.